Systematic evaluation and meta-analysis of the effectiveness of Chinese patent medicines when combined with Western medicines for treating irritable bowel syndrome - Ya-Jing Guo; Ting Li; Yu-Xi He; Yue Wu; Xiao-Jun Yang (Elsevier, 2023)
Aim: A meta-analysis was conducted to assess the effectiveness of Chinese patent medicines when used in combination with Western medicines for the treatment of irritable bowel syndrome (IBS). Methods: CNKI, Wanfang Academic Journal Full Text Database, VIP, Pubmed, Embase, Web of Science, and Cochrane Library databases were searched for clinical studies on the treatment of IBS using Chinese patent medicines that were published from inception until March 15, 2023. The shortlisted data were strictly screened and the data were extracted and evaluated, followed by data analyses and collation using RevMan 5.4 and stata16 software. Results: The final 21 randomized controlled trials(RCT), which included 14 proprietary Chinese medicines that were all orally administered, were in a total population of 2007 patients. Meta-analysis revealed that the combination of Chinese patent medicines with Western medicines could improve the overall clinical effectiveness (OR = 3.81, 95 % CI [2.84-5.12], P < 0.00001); significantly improved the abdominal pain scores (MD = -0.66, 95 % CI [-0.93, -0.40], P < 0.00001); improved the stool trait scores (MD = -0.48, 95 % CI [-0.59, -0.37], P < 0.00001); improved the IBS symptom severity scale(IBS-SSS) scores (MD = -44.36, 95 % CI [-53.64, -35.08], P < 0.00001); improved IBS quality of life(IBS-QOL) -positive (MD = 10.27, 95 % CI [3.50, 17.04], P = 0.003 < 0.05) and -negative scores (MD = -7.91, 95 % CI[-15.62, -0.02], P = 0.04 < 0.05); and improved the Hamilton Anxiety Scale(HAMA) scores (MD = -3.37, 95 % CI [-6.49, -0.24], P = 0.03); albeit no statistical difference was noted in improving Hamilton Depression Scale(HAMD) scores (MD = -2.83, 95 % CI [-5.74, 0.08], P = 0.06 > 0.05). Conclusion: For treating irritable bowel syndrome, the effectiveness of combining Chinese patent medicine with Western medicine is better than that of using Western medicine alone both in terms of relieving gastrointestinal discomfort and regulating mood. However, as the sample size was limited, it is advisable to conduct large-scale, high-quality, and rigorous randomized controlled trials to enhance the clinical evidence.